Dietary patterns are related to cognitive functioning in elderly enriched with individuals at increased risk for Alzheimer’s disease - Wesselman, L. M. P.; van Lent, D. Melo; Schröder, A.; van de Rest, O.; Peters, O.; Menne, F.; Fuentes, M.; Priller, J.; Spruth, E. J.; Altenstein, S.; Schneider, A.; Fließbach, K.; et al. (European journal of nutrition, 2021)
Purpose To investigate cross-sectional associations between dietary patterns and cognitive functioning in elderly free of dementia. Methods Data of 389 participants from the German DELCODE study (52% female, 69 ± 6 years, mean Mini Mental State Score 29 ± 1) were included. The sample was enriched with elderly at increased risk for Alzheimer’s disease (AD) by including participants with subjective cognitive decline, mild cognitive impairment (MCI) and siblings of AD patients. Mediterranean and MIND diets were derived from 148 Food Frequency Questionnaire items, and data-driven patterns by principal component analysis (PCA) of 39 food groups. Associations between dietary patterns and five cognitive domain scores were analyzed with linear regression analyses adjusted for demographics (model 1), and additionally for energy intake, BMI, other lifestyle variables and APOe4-status (model 2). For PCA-derived dietary components, final model 3 included all other dietary components. Results In fully adjusted models, adherence to Mediterranean and MIND diet was associated with better memory. The ‘alcoholic beverages’ PCA component was positively associated with most cognitive domains. Exclusion of MCI subjects ( n = 60) revealed that Mediterranean and MIND diet were also related to language functions; associations with the alcoholic beverages component were attenuated, but most remained significant. Conclusion In line with data from elderly population samples, Mediterranean and MIND diet and some data-derived dietary patterns were related to memory and language function. Longitudinal data are needed to draw conclusions on the putative effect of nutrition on the rate of cognitive decline, and on the potential of dietary interventions in groups at increased risk for AD.